2013
DOI: 10.1002/anie.201307410
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stereoselective Recognition and Deracemization of Amino Acids by Supramolecular Self‐Assembly

Abstract: The highly stereoselective supramolecular self-assembly of α-amino acids with a chiral aldehyde derived from binol and a chiral guanidine derived from diphenylethylenediamine (dpen) to form the imino acid salt is reported. This system can be used to cleanly convert D-amino acids into L-amino acids or vice versa at ambient temperature. It can also be used to synthesize α-deuterated D- or L-amino acids. A crystal structure of the ternary complex together with DFT computation provided detailed insight into the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Chin et al reported the chiral cobalt complex that successfully deracemized the coordinated amino acids, where the strong metal binding of the amino acids increased the acidity of the hydrogen on the asymmetric carbon . Our group, and also Chin's group, have developed a lot of binol aldehydes that bind amino acids through an imine bond and exhibit deracemization activity , …”
Section: Introductionmentioning
confidence: 99%
“…Chin et al reported the chiral cobalt complex that successfully deracemized the coordinated amino acids, where the strong metal binding of the amino acids increased the acidity of the hydrogen on the asymmetric carbon . Our group, and also Chin's group, have developed a lot of binol aldehydes that bind amino acids through an imine bond and exhibit deracemization activity , …”
Section: Introductionmentioning
confidence: 99%
“…In particular,compounds 1 and 2,which were reported by Chin [16] and co-workers and ourselves, [17] are considered as the best-performing ligands for the direct DKR of unprotected TM-a-AAs (Figure 1). Forb oth types of ligands,D KR proceeds via the corresponding Schiff base intermediates followed by thermodynamic equilibration of the resulting diastereomers.However,ligands 1 and 2 also share the same shortcomings:1 )They completely fail in the DKR of amino acids with tertiary side chains,a nd 2) as they are based on axially chiral 1,1'-binaphthyl moieties,they are rather expensive to rival the economic efficiencyofenzymatic methods for the large-scale preparation of TM-a-AAs.C ontinuing our work on modular approaches to chiral ligands, [18] we identi- Figure 1.…”
mentioning
confidence: 98%
“…[6,7] Among various approaches to enantiomerically pure TMa-AAs, [6][7][8] the dynamic kinetic resolution (DKR) of racemates is unarguably the most economic solution, especially on alarge scale.[9] However,the choice of methods available for such processes is overwhelmingly dominated by biocatalytic procedures, [10] whereas purely chemical methods [11] have been disproportionally underdeveloped and prohibitively expensive.[12] Therefore,t osurpass the exceptional efficiencyo f enzymatic approaches, [10] ap urely chemical method should feature an ingenious combination of simple and high-yielding reactions,o perationally convenient conditions, [13] as well as inexpensive starting materials and ar ecyclable source of chirality.A sp art of our long-term interests in the development of practical methods for the preparation of TM-a-AAs and TM-b-AAs [14, 15] and drawing inspiration from work by Chin and co-workers, [16] we have recently been focusing on the development of new types of chiral ligands that are suitable for direct and practically useful DKR reactions of unprotected TM-a-AAs.In particular,compounds 1 and 2,which were reported by Chin [16] and co-workers and ourselves, [17] are considered as the best-performing ligands for the direct DKR of unprotected TM-a-AAs (Figure 1). Forb oth types of ligands,D KR proceeds via the corresponding Schiff base intermediates followed by thermodynamic equilibration of the resulting diastereomers.However,ligands 1 and 2 also share the same shortcomings:1 )They completely fail in the DKR of amino acids with tertiary side chains,a nd 2) as they are based on axially chiral 1,1'-binaphthyl moieties,they are rather expensive to rival the economic efficiencyofenzymatic methods for the large-scale preparation of TM-a-AAs.C ontinuing our work on modular approaches to chiral ligands, [18] we identi- Figure 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6,7] Among various approaches to enantiomerically pure TMa-AAs, [6][7][8] the dynamic kinetic resolution (DKR) of racemates is unarguably the most economic solution, especially on alarge scale. [12] Therefore,t osurpass the exceptional efficiencyo f enzymatic approaches, [10] ap urely chemical method should feature an ingenious combination of simple and high-yielding reactions,o perationally convenient conditions, [13] as well as inexpensive starting materials and ar ecyclable source of chirality.A sp art of our long-term interests in the development of practical methods for the preparation of TM-a-AAs and TM-b-AAs [14,15] and drawing inspiration from work by Chin and co-workers, [16] we have recently been focusing on the development of new types of chiral ligands that are suitable for direct and practically useful DKR reactions of unprotected TM-a-AAs. [12] Therefore,t osurpass the exceptional efficiencyo f enzymatic approaches, [10] ap urely chemical method should feature an ingenious combination of simple and high-yielding reactions,o perationally convenient conditions, [13] as well as inexpensive starting materials and ar ecyclable source of chirality.A sp art of our long-term interests in the development of practical methods for the preparation of TM-a-AAs and TM-b-AAs [14,15] and drawing inspiration from work by Chin and co-workers, [16] we have recently been focusing on the development of new types of chiral ligands that are suitable for direct and practically useful DKR reactions of unprotected TM-a-AAs.…”
mentioning
confidence: 99%